Optimalisasi Pembelajaran Bahasa Arab Melalui Media Interaktif “Amplop Pintar” untuk Meningkatkan Penguasaan Mufradat Siswa di Kelas IV-A MIN 5 Bireuen - Nauratul Islami; Nazarullah (Yayasan Madinah Al-Aziziyah, 2025)
This study aims to examine the effect of using the interactive learning media “Amplop Pintar” on students’ vocabulary (mufradat) mastery in Arabic language learning. The background of this study is based on students’ low ability to retain Arabic vocabulary, which affects their language skills. This research employed a quantitative approach with an experimental method. The subjects of this study were 20 students of class IV-A at Madrasah Ibtidaiyah Negeri 5 Bireuen. Data were collected through tests, observations, and documentation. Data analysis was conducted using a paired sample t-test. The results showed an increase in the students’ mean scores from 81.16 in the pre-test to 84.33 in the post-test. The statistical test results indicated a significance value of 0.000 < 0.05, meaning that there is a significant effect of using the “Amplop Pintar” media on students’ vocabulary mastery. In addition, the use of this media also improved students’ activeness, motivation, and engagement in the learning process.